Competence of newly qualified registered nurses from a nursing college - BG Morolong; MM Chabeli (AOSIS, 2005)
The South African education and training system, through its policy of outcomesbased education and training, has made competency a national priority. In compliance to this national requirement of producing competent learners, the South African Nursing Council ( 1999 B) require that the beginner professional nurse practitioners and midwives have the necessary knowledge, skills, attitudes and values which will enable them to render efficient professional service. The health care system also demands competent nurse practitioners to ensure quality in health care. In the light of competency being a national priority and a statutory demand, the research question that emerges is, how competent are the newly qualified registered nurses from a specific nursing college in clinical nursing education? A quantitative, non-experimental contextual design was used to evaluate the competence of newly qualified registered nurses from a specific nursing college. The study was conducted in two phases. The first phase dealt with the development of an instrument together with its manual through the conceptualisation process. The second phase focused on the evaluation of the competency of newly qualified nurses using the instrument based on the steps of the nursing process. A pilot study was conducted to test the feasibility of the items of the instrument. During the evaluation phase, a sample of twenty-six newly qualified nurses was selected by simple random sampling from a target population of thirty-six newly qualified registered nurses. However, six participants withdrew from the study. Data was collected in two general hospitals where the newly qualified registered nurses were working. Observation and questioning were used as data collection techniques in accordance with the developed instrument. Measures were taken to ensure internal validity and reliability of the results. To protect the rights of the participants, the researcher adhered to DENOSA'S (1998:2.2.1) ethical standards of research. A descriptive statistical method of data analysis was used in this study. Findings revealed that newly qualified registered nurses were not competent. The highest score obtained was 51 % and the lowest score was 22% with an average score of 34.05%. The results concerning the implementation of the phases of the nursing process indicated that participants were fairly competent in terms of knowledge, skills, attitudes and values of assessment. Participants had very little knowledge of nursing diagnosis and were not competent on the skills of diagnosis. Participants lacked basic knowledge, skills, attitudes and values of the nursing process. They lacked critical thinking skills in their approach to providing quality patient care. The recommendations of the study relate to improving the system of clinical accompaniment, reviewing the clinical facilities where learners are allocated, reviewing the implementation of the curriculum, the methods of teaching and the quality assurance mechanisms that are in place. Further research is recommended on competence of newly qualified registered nurses at other nursing colleges or similar context.